Analysis and evaluation of the image of Adelais silk scarf based on grey correlation - GU Zhaohui; HU Siqi (Xi'an Gongcheng Daxue xuebao)
In order to investigate the continuation and innovation of Adelais culture in contemporary fashion and explore the effective application of Adelais silk patterns in scarves, this study meticulously selected 13 representative Adelais silk patterns from Xinjiang and arranged them into scarves with distinct pattern combinations but uniform style and design. A group of female participants aged between 18~50 years were surveyed based on the principles of sensory engineering, and the findings were subsequently analyzed by mean analysis, factor analysis, and grey correlation analysis. The results show that Adelais silk patterns significantly impact the sensory perception of scarves, with temperament constituting the principal factor that influences consumers' preference for scarves, appearance having a relatively minor effect.